Farmers’ income in India: trends and prospects for future growth - Kamal Vatta,; Parisha Budhiraja, (Agricultural Economics Research Review, 2023)
The Government of India aims to double agricultural income by 2022–23. This paper examines whether this target can be met—by analysing the trends in farmer income, sources, and factors of performance by farm class and state—and finds it unlikely. Income growth would be accelerated by improving resource use efficiency and access to agricultural extension, markets, and credit; and by diversifying towards high-value, high-growth sectors like animal husbandry and horticulture. To sustain income growth in the long term, greater resources must be allocated to agricultural research, and gainful employment opportunities must be created in the rural non-farm sector.